2013
DOI: 10.1002/smll.201300310
|View full text |Cite
|
Sign up to set email alerts
|

A Detailed Experimental and Theoretical Study into the Properties of C60 Dumbbell Junctions

Abstract: A combined experimental and theoretical investigation is carried out into the electrical transport across a fullerene dumbbell one-molecule junction. The newly designed molecule comprises two C60 s connected to a fluorene backbone via cyclopropyl groups. It is wired between gold electrodes under ambient conditions by pressing the tip of a scanning tunnelling microscope (STM) onto one of the C60 groups. The STM allows us to identify a single molecule before the junction is formed through imaging, which means un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
23
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(27 citation statements)
references
References 69 publications
4
23
0
Order By: Relevance
“…This might suggest that the fluorene moiety could attach to the tip which would further stabilize the molecular junctions in the G L 1 state as it was found in Ref. 37.…”
supporting
confidence: 56%
See 1 more Smart Citation
“…This might suggest that the fluorene moiety could attach to the tip which would further stabilize the molecular junctions in the G L 1 state as it was found in Ref. 37.…”
supporting
confidence: 56%
“…27 all observed values are in the range log(G/G 0 ) = -1.0 to 0.2. 29,37,54,55,[58][59][60][61][62][63][64][65] The difference in conductance (up to factor of 20) 55 of these distinct states is, however, much lower than that one of the two well-discernible G H 1 and G L 1 features that we resolved for 1 (compare blue and red trend lines in Figure 4). We suggest therefore that different contact geometries of the C 60 anchoring groups cannot account for the existence of these two distinctly observed conductance states of molecule 1.…”
mentioning
confidence: 62%
“…Other larger footprint or multiple attachment point chemicontacts have been investigated, including fullerene contacts (66,67) and tripodal (68) anchoring groups. The fullerene terminated molecular wires are particularly interesting given they can be imaged with an STM before making single-molecule measurements, thereby guaranteeing that only one molecule is wired into the junction (66,67).…”
Section: Anchoring Groups and Contactsmentioning
confidence: 99%
“…Other larger footprint or multiple attachment point chemicontacts have been investigated, including fullerene contacts (66,67) and tripodal (68) anchoring groups. The fullerene terminated molecular wires are particularly interesting given they can be imaged with an STM before making single-molecule measurements, thereby guaranteeing that only one molecule is wired into the junction (66,67). Measurements of dumbbell molecular wires consisting of two C 60 terminal groups connected through a fluorene and cyclopropyl linker have shown that individual molecules can be repeatedly lifted and pressed back onto the surface, although the highest conductance state was inferred to involve contact between the STM tip and central fluorene group (66).…”
Section: Anchoring Groups and Contactsmentioning
confidence: 99%
“…However, transmission at the tip/C 60 interface is reduced due to the limited number of states on the monoatomic gold tip, and most of the electronic wavefunctions are reflected back into the fullerene cage. 29,30 As a result, a δ − charge builds up on C 60 , which raises the energy of the LUMO and prevents HOMO/LUMO level crossing. Preliminary simulations suggest that a stronger coupling between the gold contact and the C 60 enables the HOMO and LUMO to cross more easily and a full analysis will be the subject of a future paper.…”
mentioning
confidence: 99%